1987
DOI: 10.1152/ajpregu.1987.252.6.r1039
|View full text |Cite
|
Sign up to set email alerts
|

Activation of neurosecretory cells by osmotic stimulation of anteroventral third ventricle

Abstract: Extracellular action potentials of paraventricular neurosecretory cells were obtained from urethan-anesthetized rats during microinjection of a hyper- or hypotonic solution into the anteroventral third ventricle (AV3V), third ventricle, or the vicinity of the recording site. The injection of a 0.2-microliter NaCl solution with a concentration range from 0.16 to 0.8 M into the AV3V excited most of the neurons tested. However, the magnitude of the response was dose related. In most cases, arterial blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…Many studies have shown that ablation of the AV3V which includes the OVLT (one of the CVOs) results in the reduction or abolishment of osmoreception for vasopressin release or antidiuresis in dogs (THRASHER et a!., 1982) and in rats (JOHNSON et a!., 1978;SLADEK and JOHNSON, 1983;GRUBER et a!., 1986). Furthermore, we have observed that microinjection of hypertonic NaCI solution into the AV3V excited not only putative vasopressin neurones but also putative oxytocin neurones (HONDA et a!., 1987). We therefore attempted to determine the effect of the AV3V lesion on the plasma oxytocin concentration and found that the lesion abolished the response of oxytocin release to the osmotic stimuli.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Many studies have shown that ablation of the AV3V which includes the OVLT (one of the CVOs) results in the reduction or abolishment of osmoreception for vasopressin release or antidiuresis in dogs (THRASHER et a!., 1982) and in rats (JOHNSON et a!., 1978;SLADEK and JOHNSON, 1983;GRUBER et a!., 1986). Furthermore, we have observed that microinjection of hypertonic NaCI solution into the AV3V excited not only putative vasopressin neurones but also putative oxytocin neurones (HONDA et a!., 1987). We therefore attempted to determine the effect of the AV3V lesion on the plasma oxytocin concentration and found that the lesion abolished the response of oxytocin release to the osmotic stimuli.…”
Section: Discussionmentioning
confidence: 48%
“…And it is now widely accepted that there are cranial osmoreceptors for vasopressin release, which are excited when the receptor cells are dehydrated due to withdrawal of water from the cells by osmotic agents which hardly permeate the cell membrane, such as NaCI, sucrose and mannitol (SLADEK and KNIGGE, 1977;THRASHER et al, 1980a, b) although the precise location of the osmoreceptors is somewhat controversial (LENG et al, 1982;THRASHER et al, 1982;SLADEK and JOHNSON, 1983;HONDA et al, 1987). Recently it has been shown that oxytocin, the other neurohypophysial hormone, is also secreted in response to hypertonlc NaCI In rats (JONES and PICKERING,1969;BRIMBLE et al, 1978;BALMENT et al, 1980).…”
mentioning
confidence: 99%
“…Furthermore, intracellular recordings in hypothalamic explants have indicated that OVLT neurones projecting to the supraoptic nucleus can be excited by hypertonic stimuli (Nissen, Bourque & Renaud, 1993), suggesting that these cells may relay osmotic information to hypothalamic MNCs. In agreement with this hypothesis, local osmotic stimulation of the anteroventral region of the third ventricle has been shown to modulate the frequency of firing of hypothalamic MNCs in vivo (Honda, Negoro, Higuchi & Tadokoro, 1987) and in vitro (Richard & Bourque, 1992). In this study, we have examined the processes underlying the effects of local osmotic stimulation of the OVLT during intracellular recordings obtained from supraoptic nucleus MNCs in superfused explants of rat hypothalamus.…”
mentioning
confidence: 76%
“…Only a small number of these cells were tested for osmosensitivity but two of the four OD + cells were excited by the osmotic stimulus and two of the three OD-cells were inhibited. (Thrasher, Keil & Ramsay, 1982), cells in the region are osmosensitive (Sayer et al 1984) magnocellular neurosecretory cells (Honda et al 1987), it is reasonable to suggest that osmosensitive elements in the AV3V region provide osmotic drive to the supraoptic nucleus. The present investigation was undertaken to provide electrophysiological evidence for such a direct connection between the two regions.…”
Section: Recordings From Cells In the A V3v Regionmentioning
confidence: 99%